Direct-acting Antivirals Induce Lymphoproliferative Disease Response in HCV-infected Patients: A Prospective Case Series. (4th October 2017) - Hosry, Jeff; Economides, Minas; Samaniego, Felipe; Torres, Harrys
Abstract: Background: Hepatitis C virus (HCV) infection is associated with the development of B-cell Non-Hodgkin lymphoma (NHL). Several studies report regression of indolent NHL in HCV-infected patients treated with interferon (IFN)-containing therapy without chemotherapy. We are describing, herein, the oncologic response of patients with such cancers treated with only direct antiviral agents (DAAs). Methods: Patients with HCV-associated NHL seen at MD Anderson Cancer Center (6/2014 to 6/2017) and treated with DAAs were followed and those with indolent NHL treated with DAAs were further analyzed. DAA regimens were administered according to guidelines for HCV-infected patients without cancer. Efficacy was calculated on the basis of achieving sustained virologic response 12 weeks (SVR12) after end of treatment (EOT). NHL status was evaluated at the time of DAAs initiation and response was prospectively analyzed at 6 months after EOT using WHO criteria. Results: Six patients received DAAs alone as first-line management of their NHL. Most patients 5/6 (83%) did respond to such treatment avoiding or delaying the use of chemotherapy (Table). Conclusion: As described with IFN-containing therapy, the oncologic outcome of HCV-infected patients with indolent NHL could also improve by using only DAAs. Disclosures: H. Torres, Gilead Sciences: Consultant and Grant Investigator, Consulting fee, Grant recipient and Research support. Merck & Co: Consultant and Grant Investigator, Consulting fee and Grant recipient. Janssen Pharmaceuticals, Inc.: Consultant, Consulting fee. Dynavax Technologies: Consultant, Consulting fee